Peran Bahasa Indonesia dalam Meningkatkan Pemahaman Materi Pembelajaran Pendidikan Jasmani, Kesehatan dan Rekreasi - Ika Febriana; Aqilah Ramadhani Parinduri; Fauziah Amanda Rambe; Maulana Ikhwan; Dimmichael Ginting (Lembaga Pengembangan Kinerja Dosen, 2024)
Physical education plays an important role in shaping the mental and physical health of students, especially in the context of the Physical Education, Health, and Recreation (PJKR) study program at Medan State University. Indonesian is one of the languages ​​that can be used in PJKR learning. Indonesian can be used in PJKR learning to communicate with friends and teachers while studying at college, as well as to understand sports instructions and regulations. The purpose of this study was to determine how much Indonesian contributes to improving learning materials related to physical education, health, and recreation. The role of physical education, health, and recreation in improving the mental and physical health of students in the Physical Education, Health, and Recreation study program at Medan State University was studied using a qualitative research methodology in the form of literature review and interviews.